1992
DOI: 10.1111/j.1432-1033.1992.tb17444.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of carboxypeptidase‐Y‐catalysed peptide semisynthesis

Abstract: The initial rate steady-state kinetics of carboxypeptidase-Y-catalyzed hydrolysis and aminolysis reactions with some a-N-benzoyl-L-tyrosinyl compounds has been investigated using L-valinamide as the nucleophile in aminolysis. Hydrolysis of a-N-benzoyl-L-tyrosinyl ethyl ester, 4-nitroanilide, and -amide has been studied in the pH range 4 -9. The results are interpreted in terms of the classical serine proteinase mechanism, which involves enzyme-substrate complex formation, followed by acylation and deacylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Two possibilities exist: hydrolysis at low pH may take place by a mechanism different from that of the serine endopeptidases, or alternatively, the p of His397 is below 3.0 and is not the 4.47 value on which kQÍt is dependent in the pH range investigated in this study. The pH profile of fccat for the hydrolysis of the ester substrate Bz-Tyr-OEt (Christensen et al, 1992) is similar to that reported here for a peptide substrate, and consequently, it is unlikely that the unusual shape of the pH profile is determined by the carboxylate group of the peptide substrate. With the double mutant N51A+E145A the pH profile for Arcat yields a pA"a identical to the value obtained with the wild-type enzyme, demonstrating that the ionization of the residue influencing fccat is not perturbed by the residues involved in binding of the C-terminal carboxylate group.…”
Section: Substratesupporting
confidence: 81%
“…Two possibilities exist: hydrolysis at low pH may take place by a mechanism different from that of the serine endopeptidases, or alternatively, the p of His397 is below 3.0 and is not the 4.47 value on which kQÍt is dependent in the pH range investigated in this study. The pH profile of fccat for the hydrolysis of the ester substrate Bz-Tyr-OEt (Christensen et al, 1992) is similar to that reported here for a peptide substrate, and consequently, it is unlikely that the unusual shape of the pH profile is determined by the carboxylate group of the peptide substrate. With the double mutant N51A+E145A the pH profile for Arcat yields a pA"a identical to the value obtained with the wild-type enzyme, demonstrating that the ionization of the residue influencing fccat is not perturbed by the residues involved in binding of the C-terminal carboxylate group.…”
Section: Substratesupporting
confidence: 81%
“…a-Chymotrypsin-catalysed acyl-transfer and, in general, acyl-transfer reactions catalysed by serine proteases proceed without formation of the ESN complex (Scheme 3). P1 p Scheme 3 Scheme 3 was made using the results of this work and the previously referred studies of a-chymotrypsin, as well as previous studies of trypsin, carboxypeptidases Y and W and alkaline mesentericopeptidase (Seydoux et al, 1969;Riechman andKasche, 1984, 1985;Shima et al, 1987;Bratovanova et al, 1988;Christensen et al, 1992).…”
Section: Analysis Of the Kinetic Modelmentioning
confidence: 96%
“…The increased size of the ester group may have hindered the optimal binding of the amino-acid esters to CPDY, and as a result, hydrolysis dominated. 23,32 The yields of the oligo(L-leucine), oligo(L-isoleucine) and oligo(L-valine) peptides were 76.6%, 81.3% and 77.9%, respectively, indicating that a small change in the chemical structure of the amino-acid side chains did not influence the aminolysis yields. In contrast, the molecular weights of the oligo(L-leucine), oligo(L-isoleucine) and oligo(L-valine) peptides were 612, 680 and 620 Da, respectively.…”
Section: Type Of Amino Acidsmentioning
confidence: 97%
“…A kinetic model for serine protease-catalyzed peptide synthesis has been proposed. 19,[22][23][24][25][26] This model suggests that the protease-catalyzed synthesis of peptides proceeds via kinetically controlled synthesis. The activated amino acid and the enzyme first form an acyl-enzyme intermediate (ES complex) (Scheme 1), which is then competitively deacylated by a nucleophile or water.…”
Section: Introductionmentioning
confidence: 99%